TO STUDY THE PREVALENCE OF SARCOPENIA IN TYPE-2 DIABETIC PATIENTS IN A RURAL TERTIARY CARE HOSPITAL - Bansal, Yatharth; Kumari, Savita (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of this study was to study the prevalence of sarcopenia in type-2 diabetic population coming to a rural tertiary care hospital. Methods: A cross-sectional study involving 150 participants including both outpatient and inpatient department patients was conducted at MM Institute of Medical Sciences and Research, Mullana (Ambala) between June 2021 and June 2022 after seeking appropriate permissions and approval from the Institutional Ethics Committee. Patients who consented to participation were enrolled in the study and were evaluated as per the European working group for sarcopenia in older people algorithm using bioelectrical impedance analysis and were asked to fill out a printed proforma (available in Hindi and English languages) to assess their SARC-CalF scores, handgrip strength, calf circumference and comorbidities. Patients were interviewed if they were illiterate, and responses were recorded. Statistical analyses were performed on IBM SPSS Statistics version 26. Results: The overall prevalence of sarcopenia was found to be 3.3% in 150 subjects who were enrolled in the study. Among the cases (diabetics), the prevalence was 4.0% and 2.67% in the controls (non-diabetics). Mean handgrip strength was found to be 18.73 kg among cases and 19.47 kg among controls. Handgrip strength did not show a significant association with diabetes (p=0.435). Handgrip strength was not found to be significantly associated to sex. Mean gait speed (in m/s) was found to be 1.42 in a range of 0.30–2.50 with a standard deviation of 0.59. Mean gait speed was 1.87 m/s in controls and 0.96 m/s in cases. Gait speed was found to be significantly associated with diabetes (p=0.00). No significant association was seen with sex (p=0.95). Mean calf circumference was found to be 33.28 cm among cases and 34.49 cm in controls. Calf circumference was found to be significantly correlated with diabetes (p=0.00). The SARC-CalF questionnaire was shown to have a sensitivity of 40% and a specificity of 100% at the recommended threshold of ≥11. In the study group, the mean HbA1c was found to be 10.1%. Sarcopenia was not found to be significantly associated with diabetes (p=0.649). No statistically significant relationship was found between hypertension and sarcopenia (p=0.394). Conclusion: Sarcopenia is largely an overlooked disease, especially in India. Various efforts to study the prevalence, causation, and effects of sarcopenia have been made, but no large-scale studies have been undertaken so far. Our study concluded that the SARC-CalF questionnaire can be used as a bedside screening tool. Though our study failed to find any statistically significant relationship between sarcopenia and diabetes, large scale studies are still warranted in this regard.